And God Said What? An Introduction to Biblical Literary Forms - Nalkara, Benny (Asian Horizons, 2011)
Margaret Nutting Ralph, And God Said What? An Introduction to Biblical Literary Forms, Bangalore: Theological Publications in India, 2011 (revised edition). Pages: 307. ISBN 978-81- 888821-69-3